Question and Answers Forum

All Questions      Topic List

Mensuration Questions

Previous in All Question      Next in All Question      

Previous in Mensuration      Next in Mensuration      

Question Number 28808 by ajfour last updated on 30/Jan/18

Answered by ajfour last updated on 30/Jan/18

taking A as origin,  and ∠AED=α =tan^(−1) 2  eq. of AC          y=x  eq. of DE        y=a−2x  F lies on both lines  so  x_F  =y_F =(a/3)  (r_1 /(cot 22.5°+cot ((α/2)))) = (a/2)  let cot 22.5° =(1/m_1 )  ((2m_1 )/(1−m_1 ^2 ))=1  ⇒   m_1 ^2 +2m_1 =1  m_1 =((−2+2(√2))/2) = (√2)−1  (1/m_1 ) = (√2)+1  let  tan (α/2)=m  tan α==((2m)/(1−m^2 )) = 2  ⇒    2m^2 +2m−2=0  or   m=((−2+2(√5))/4) = (((√5)−1)/2)        cot (α/2)= (1/m) = (((√5)+1)/2)   As    r_1 (cot 22.5°+cot (𝛂/2))=(a/2)   ,  r_1 =((a/2)/((√2)+1+(((√5)+1)/2))) =(a/(2(√2)+(√5)+3))  ....       tan (45°−(α/2))=((1−((((√5)−1)/2)))/(1+(((√5)−1)/2)))         =((3−(√5))/(1+(√5))) =   cot (45°−(α/2))=((1+(√5))/(3−(√5))) =((3+5+2(√5))/4)           = 2+((√5)/2)      r_2 (cot 22.5°+cot (45°−(α/2))= a  ⇒  r_2 =(a/((√2)+3+((√5)/2)))  .....      cot (45°+(α/2))=tan (45°−(α/2))         =((3−(√5))/((√5)+1)) =((4(√5)−8)/4) =(√5)−2    r_3 [cot 22.5°+cot (45°+(α/2))]= a  ⇒  r_3 =(a/((√2)+(√5)−1))  .......

takingAasorigin,andAED=α=tan12eq.ofACy=xeq.ofDEy=a2xFliesonbothlinessoxF=yF=a3r1cot22.5°+cot(α2)=a2letcot22.5°=1m12m11m12=1m12+2m1=1m1=2+222=211m1=2+1lettanα2=mtanα==2m1m2=22m2+2m2=0orm=2+254=512cotα2=1m=5+12Asr1(cot22.5°+cotα2)=a2,r1=a/22+1+5+12=a22+5+3....tan(45°α2)=1(512)1+512=351+5=cot(45°α2)=1+535=3+5+254=2+52r2(cot22.5°+cot(45°α2)=ar2=a2+3+52.....cot(45°+α2)=tan(45°α2)=355+1=4584=52r3[cot22.5°+cot(45°+α2)]=ar3=a2+51.......

Answered by mrW2 last updated on 30/Jan/18

AF=((AC)/3)=((√2)/3)a  EF=((ED)/3)=(1/3)×((√5)/2)a=((√5)/6)a  FC=(2/3)AC=((2(√2))/3)a  FD=(2/3)ED=((√5)/3)a    Using general formula:  r=(√(((s−a)(s−b)(s−c))/s))    Circle 1 in ΔAEF:  s=(1/2)((1/2)a+((√5)/6)a+((√2)/3)a)=((3+(√5)+2(√2))/(12))a  r_1 =a(√(((((3+(√5)+2(√2))/(12))−(1/2))(((3+(√5)+2(√2))/(12))−((√5)/6))(((3+(√5)+2(√2))/(12))−((√2)/3)))/((3+(√5)+2(√2))/(12))))  r_1 =(a/(12))(√((((√5)+2(√2)−3)(3+2(√2)−(√5))(3+(√5)−2(√2)))/(3+(√5)+2(√2))))  ⇒r_1 =(a/(12))(√(2(9−4(√2)−(√5))))≈0.12a    Circle 2 in ΔAFD:  s=(1/2)(a+((√2)/3)a+((√5)/3)a)=((3+(√2)+(√5))/6)a  r_2 =a(√(((((3+(√2)+(√5))/6)−1)(((3+(√2)+(√5))/6)−((√2)/3))(((3+(√2)+(√5))/6)−((√5)/3)))/((3+(√2)+(√5))/6)))  r_2 =(a/6)(√(((−3+(√2)+(√5))(3−(√2)+(√5))(3+(√2)−(√5)))/(3+(√2)+(√5))))  ⇒r_2 =(a/6)(√(2(12−7(√2)−5(√5)+3(√(10)))))≈0.15a    Circle 3 in ΔDFC:  s=(1/2)(a+((√5)/3)a+((2(√2))/3)a)=((3+(√5)+2(√2))/6)a  r_3 =a(√(((((3+(√5)+2(√2))/6)−1)(((3+(√5)+2(√2))/6)−((√5)/3))(((3+(√5)+2(√2))/6)−((2(√2))/3)))/((3+(√5)+2(√2))/6)))  r_3 =(a/6)(√(((−3+(√5)+2(√2))(3−(√5)+2(√2))(3+(√5)−2(√2)))/(3+(√5)+2(√2))))  ⇒r_3 =(a/6)(√(2(9−4(√2)−(√5))))=2r_1 ≈0.25a    Circle 4 in ΔABC:  s=(1/2)(a+a+(√2)a)=((2+(√2))/2)a  r_4 =a(√(((((2+(√2))/2)−1)(((2+(√2))/2)−1)(((2+(√2))/2)−(√2)))/((2+(√2))/2)))  r_4 =(a/2)(√(2(3−2(√2))))≈0.29a

AF=AC3=23aEF=ED3=13×52a=56aFC=23AC=223aFD=23ED=53aUsinggeneralformula:r=(sa)(sb)(sc)sCircle1inΔAEF:s=12(12a+56a+23a)=3+5+2212ar1=a(3+5+221212)(3+5+221256)(3+5+221223)3+5+2212r1=a12(5+223)(3+225)(3+522)3+5+22r1=a122(9425)0.12aCircle2inΔAFD:s=12(a+23a+53a)=3+2+56ar2=a(3+2+561)(3+2+5623)(3+2+5653)3+2+56r2=a6(3+2+5)(32+5)(3+25)3+2+5r2=a62(127255+310)0.15aCircle3inΔDFC:s=12(a+53a+223a)=3+5+226ar3=a(3+5+2261)(3+5+22653)(3+5+226223)3+5+226r3=a6(3+5+22)(35+22)(3+522)3+5+22r3=a62(9425)=2r10.25aCircle4inΔABC:s=12(a+a+2a)=2+22ar4=a(2+221)(2+221)(2+222)2+22r4=a22(322)0.29a

Commented by ajfour last updated on 30/Jan/18

Splendid! Sir .

Splendid!Sir.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com